EVOLUTIONARY ASPECTS EXPLIOTATION OF CHICKPEA CHLOROTIC DWARF VIRUS (CPCDV)INFECTING COTTON AND CHICKPEA - ATIF, M; AHMAD, F; MANZOOR, MT; GILANI, K; ALI, Q; SARWAR, M; ANJUM, S; ALAM, MW; HUSSIAN, A; RAFAQAT, N (Biological and Clinical Sciences Research Journal, 2022)
The Chickpea Chlorotic Dwarf Virus (CpCDV) has been found highly devastating not only for chickpea crop but also for lentils, cotton and papaya. In recent past years, this mastrevirus caused a sublime pressure on the hosts and reduced yield up to 95%. This virus is most prevalence in dry regions and equally important pathogen in other parts of the world especially in America and Europe. This capability is due to rapid changes in DNA. Vector species also play an important role in spread of this virus. In our current study the evolutionary study of 53 genomes was performed. All genomes obtained from cotton crops are ancestors and rest is offsprings. According to our finding, CpCDV is very important pathogen not only for Fabaceae family but also for Malvaceae family.